Mechanical and Structural Studies of Ternary Mo–Zr–N Layers Deposited on Substrate by PVD - Abboudi, Abdelaziz; Chermime, Brahim; Djebaili, Hamid; Brioua, Mourad (Металлофизика и новейшие технологии, 2017)
Our study of ternary Mo–Zr–N thin layers is novel with the objective of improving certain mechanical and tribological characteristics and of finding the appropriate stoichiometry to have the microstructure, which orientates to the desired properties, using the characterization techniques: SEM, XRD, EDS, XPS, WDS and similar methods as well as nanoindentation, alternative tribometry and scratch test.